Estrategias empresariales peruanas en la primera globalización: participación temprana en exposiciones internacionales - Seiner, Lizardo (2018)
Universal Exhibitions (EXPO), date from 1850, and represent a powerful international event to encourage progress, the promotion of development and a visible expression of the process of globalization. In Peru, the press severely criticized that the nation did not attend to the 2015 EXPO. It is hence worth asking if this was first time the country did not participate in one of these events. This essay, in this context addresses. The relevance of the EXPO, as it analyses their contributions, to the above from a historical perspective, and points out its usefulness to adding value in businesses. Given EXPO resonance, for the purpose of positioning a national image, it is also seen as necessary to review, in ending, the relationships between The Government and private firms within the framework of commercial policies.